Resonant enhancement of neutrinoless double-electron capture in 152Gd - Eliseev, Sergey; Roux, C.; Blaum, Klaus; Block, M.; Droese, C.; Herfurth, Frank; Kluge, Heinz-Jürgen; Krivoruchenko, M. I.; Novikov, Yu. N.; Minaya Ramirez, E.; Schweikhard, L.; Shabaev, V. M.; et al. (Physical review letters, 2011)
In the search for the nuclide with the largest probability for neutrinoless double-electron capture, we have determined the Qϵϵ value between the ground states of 152Gd and 152Sm by Penning-trap mass-ratio measurements. The new Qϵϵ value of 55.70(18) keV results in a half-life of 1026 yr for a 1 eV neutrino mass. With this smallest half-life among known 0νϵϵ transitions, 152Gd is a promising candidate for the search for neutrinoless double-electron capture.
Im Titel ist die Zahl 152 hochgestellt
Gesehen am 12.04.2022